A Comparative Analysis of the Effect of Various Denture Adhesives Available in Market on the Retentive Ability of the Maxillary Denture: An In Vivo Study - Kumar, Manmohit Singh (Springer-Verlag, 2011)
“Every human being has a divine right to enjoy the health to its fullest.” Oral and Dental health is not an exception to this dictum. The speciality of Prosthodontics has emerged as a science to provide replacement of missing dentition for its form and functions along with associated structures. Any successful complete denture treatment combines exemplary technique, effective patient rapport, patient education, and familiarity with all possible management options in order to provide maximum satisfaction to patient. There are some forcing situations where providing desirable (optimal) retention may be a problem. In such types of patients use of denture adhesives is recommended for enhancing the quality of retention. The use of denture adhesive provides comfort and additional confidence not only by increasing the adhesive and cohesive but also eliminating voids between the denture base and the basal seat. This study is undertaken to evaluate the enhancement of retentive quality of complete denture with the use of denture adhesives available in Indian markets for the use by denture wearers.